Retrocaval Ureter: An Incidental Finding of a Rare Cause of Hydronephrosis in Adult - Muhammad, Isa H.; Umar, Bashir M.; Mustapha, Mohammed A. (Nigerian Journal of Basic and Clinical Sciences, 2024)
Rarely, hydronephrosis can be caused by the retrocaval ureter. Its rarity and vague appearance make a proper diagnosis difficult for surgeons and radiologists to make. For successful surgical care, it is crucial to distinguish different causes of urinary tract obstruction, particularly urolithiasis, which is more prevalent.In the current standard of care, intravenous urography (IVU) is quickly being replaced with computed tomography urography (CTU) when evaluating patients who have hydronephrosis due to suspected urolithiasis, particularly ureterolithiasis. A retrocaval ureter, being the rarest cause of hydronephrosis in adults, can be accurately diagnosed using CTU, which shows its typical appearance.We reported a case of a 41-year-old man who presented with left flank pain, for which his surgeon suspected obstructive renal calculi. On investigations, however, we found a retrocaval ureter on the right side with resultant moderate hydroureteronephrosis. We therefore demonstrate the value of CTU in determining rare causes of hydronephrosis, as it exemplifies this circumstance.Retrocaval ureter is a rare cause of hydronephrosis and may be one of the challenging cases for urologists that require careful investigations, especially when asymptomatic.
Keywords: Asymptomatic; CTU; hydroureteronephrosis; retrocaval ureter